A long way to the man (sources, ideals, ideologies) - Alexandr E. Razumov (Moscow Polytechnic University, 2022)
Today a man is facing a crucial problem: he must choose, which way to take: either hefollows one of the roads to humanism, or, if he chooses otherwise, mankind may be doomed to untimely extinction. Here we find tangled in one knot various components of mythological, religious, philosophical and scientific thinking.